Evaluation of Knowledge, Attitude, and Practice of Mothers Presenting to Pediatric Clinic Regarding Urinary Tract Infection Prevention in Children - Fazel, Mojtaba; Tefagh, Ghazaleh; Mohammadi-Vajari, Mohammad-Ali; Meysamie, Alipasha; Javadi Larijani, Faezeh; Nourbakhsh, Seyed MohammadKazem; Ravanshad, Yalda; Mojtahedi, Sayed Yousef; Abbasi, Arash (Journal of Pediatric Nephrology, 2019)
Introduction: Urinary tract infection is one of the most common bacterial infections in children. It is preventable in many cases and appropriate health behaviors can protect a child from the disease or minimize its risk. Considering the relatively high prevalence of urinary tract infections in children and with regard to the important role of healthy behaviors in preventing this infection, we decided to evaluate the knowledge, attitude and practice of mothers regarding the prevention of urinary tract infections. Materials and Methods: This cross-sectional descriptive-analytic study was performed in the Pediatric Clinic of Imam Khomeini Hospital to determine the knowledge, attitude, and practice of mothers about UTI in children and to evaluate its relationships with some demographic features. The data collection tool was a researcher-made questionnaire based on the literature review. The collected data were analyzed using SPSS 22 software and P-values less than 5% were considered significant. Results: One hundred and fifteen mothers who presented to the Pediatric Clinic of Imam Khomeini Hospital participated in this study. The average knowledge, attitude, and practice score in the first part and the practice score in the second part was 6.21, 47.85, 13.86, and 10.66, respectively. A statistically significant relationship was found between the score of knowledge and attitude. The knowledge score had a significant relationship between maternal employment status, household income, and household location. There was also a significant relationship between access to information and both the knowledge and attitude scores. Conclusions: The significant relationship between access to information resources and the maternal knowledge and attitude scores confirms the importance of awareness in improving the knowledge of mothers in preventing urinary tract infection. Keywords: Knowledge; Attitudes; Practice; Urinary Tract Infections; Pediatrics.